Hearing Impairment from the Islamic Perspective: A Review - Rahmat, Sarah; Othman, Nur Ain; Sulaiman, Nur Hafizah; Jusoh, Masnira; Izani, Mohammad Haseef; Dzulkarnain, Ahmad Aidil Arafat; Zakaria, Nur ‘Azzah; Tukiran, Nur Hanisah; Ismail, Noraidah; Marina Lamri, Marina L. Alisaputri @; Jamaluddin, Saiful Adli; Marhaban, Juliana Aminah; et al. (IIUM Medical Journal Malaysia, 2018)
Introduction: This discussion paper aims to synthesise available literature on hearing sciences from Islamic perspective and to relate this to the current hearing care practices. The paper focuses on several main scopes: i) the importance of sense of hearing from Islamic and scientific perspectives ii) impacts of hearing impairment iii) limitations in understanding and practicing Islamic teaching due to hearing impairment, iv) Islamic responsibility towards people with hearing impairment, v) current available methods to facilitate Islamic practices among hearing impaired people, and vi) incorporating Islamization in hearing care practice. Design: Narrative review and synthesis Method: Related publications and references were identified through several ways: i) by structured searches in PubMed, Google scholar, Web of Knowledge and Science Direct using the combinations of ‘Islam’, ‘hearing impairment’, ‘hearing loss’, ‘hearing’, ‘social’, learning’, ‘memory’, ‘disability’, ‘Islamic responsibility’, and ‘learning for deaf’ as key words, ii) by inspecting the reference lists of relevant articles, and iii) by identification of relevant references from Quran and Hadith by authors who have background in Quranic studies. Results: The number of publications within the audiology field, which address the aforementioned scopes, is rather limited. Additionally, a review and synthesis of literature from other related fields such as medical, health, and education, with references from Quran and Hadith, were also carried out to facilitate the discussion of the above mentioned scopes. Conclusion: This paper concludes that there is an emerging trend for the studies of hearing and Islam in the literature. Facilitating hearing impaired people in understanding and practicing Islam becomes a shared obligation for parents, society, and the patients themselves. This discussion also identifies that there is a need for more contributions from Muslim scholars in integrating and implementing the Islamic principles in current hearing care practices.